Validated High Performance Liquid Chromatography Method for Simultaneous Estimation of Paracetamol and Aceclofenac in Tablet Dosage Forms - HARIKRISHNAN*, N.; GUNASEKARAN, V.; SATHISHBABU, A.; SRINIVASARAO, G.; ROOSEWELT, C. (Asian Journal of Chemistry, 2010)
A simple, specific, precise and rapid HPLC method hasbeen developed for estimation of paracetamol and aceclofenacsimultaneously in tablet dosage form. In this methodstandard solution and sample solution of paracetamol andaceclofenac were applied on C18 reversed phase column witha mobile phase consisting of methanol, buffer, water andacetonitrile (85:15:25:5 v/v/v/v) at a flow rate of 1 mL/minand spectrophotometric detection was carried out at 274 nm.This HPLC system was quantitatively evaluated in terms oflinearity, accuracy, precision, repeatability and specificityproving the utility in estimation of drug content in tabletdosage forms.